Optimization of Indoor Production of Fresh Water Rotifer, Brachionus calyciflorus, b: Feeding Studies - Ashraf, Muhammad; Ullah, Sana; Rashid, Tariq; Ayub, Mohammad; Bhatti, Ehsan Mahmood; Naqvi, Sajid Ali; Javaid, Muhammmad (Pakistan Journal of Nutrition, 2010)
Brachionus calyciflorus is commonly found in fresh water ponds. Its production depends on unrelenting supply of Chlorella in sufficient quantity. In the current studies a water sample was collected from fish culture ponds by Wisconsin plankton net (64 μm mesh). The freshly collected stock was concentrated and fractionated by passing through 600, 200, 125, 75 and 38 μm sieves arranged vertically with gradual decrease in pore size. The pure Brachionus calyciflorus were fed on Chlorella available in the laboratory. Algae was gradually replaced by yeast to reduce dependency on labour intensive live food. Maximum number of rotifers 413 ml-1, was observed when they were fed on 160:32 yeast:algae ratio by weight combination. Ciliates and cyclops posed a major threat during culture and frequent crashes were observed due to this menace. Cyclops were selectively eradicated from the rotifer culture at 0.09 DDVP after 20 h of exposure but not ciliates. There was no selective mortality in ciliates at any stage. Nevertheless both ciliates and rotifers were dead at 0.2 ppm. Simple method of cyst preservation is mentioned.